Prevalence of Cryptosporidium in goats in Terengganu - Soffian, Sharmeen Nellisa; Hashim, Najat; Hisamuddin, Nur Hazirah; Raja Abdul Rahman, Raja Nur Rahifah Inani; Barudin, Mohd Aiman; Abdul Wahab, Ridhwan; Mohammad, Mardhiah; Md Isa, Muhammad Lokman; Mat Yusof, Afzan (2016)
A cross sectional study on Cryptosporidium in goats at farms in Terengganu was conducted from February to October 2015. In this study, an attempt was made to determine the prevalence of Cryptosporidium oocysts in the faeces of 454 goats from four selected farms in Terengganu. The oocysts were isolated using formol-ether concentration method and stained by modified Ziehl-Neelsen staining. Overall prevalence of Cryptosporidium was 48.7% (221/454). Therefore, better animal husbandry practices by the animal handlers and farmers with well-coordinated sanitary monitoring by the field veterinarians are greatly recommended to reduce the occurrence of infections.